Starfish [videorecording (DVD)] - Gardner, Virginia, 1995-; Masterson, Christina; Beecroft, Eric; White, A. T. (Starfish Pictures, LLC, 2019)
With reality fraying at the edges, Aubrey finds herself following a string of mixtapes left by her dead friend. The clues unravel the secrets of a mysterious signal: one that could either save the world--or condemn it.